Genomics of Klebsiella pneumoniae ST16 producing NDM-1, CTX-M-15, and OXA-232. (March 2019) - Espinal, P.; Nucleo, E.; Caltagirone, M.; Mattioni Marchetti, V.; Fernandes, M.R.; Biscaro, V.; Rigoli, R.; Carattoli, A.; Migliavacca, R.; Villa, L.
Abstract: Objectives: Genomic characterization of the internationally spread sequence type (ST) 16 carbapenem-resistant Klebsiella pneumoniae . Methods: The complete genomes of three carbapenem producing ST16 K. pneumoniae from Italian patients were analysed by single-nucleotide polymorphism-based phylogeny, core genome multilocus sequence typing, resistance, plasmid, and virulence content and compared with ten genomes of ST16 strains isolated in other countries. Plasmids carrying bla NDM-1 or bla OXA-232 carbapenemase genes were assembled and sequences were analysed. Results: The internationally spread ST16 K. pneumoniae clone showed variability in terms of distribution of NDM-1 and OXA-232 type carbapenemases. In some ST16 strains, up to six plasmids can be simultaneously present in the same cell, including ColE-like plasmids carrying bla OXA-232 and IncF plasmids carrying bla NDM-1 . The differences observed in plasmid, resistance, and virulence content and core genome suggested that there is not a unique, highly conserved ST16 clone, but instead different variants of this lineage circulate worldwide. Conclusions: The ST16 K. pneumoniae clone has spread worldwide and may become a high-risk clone.